2020
DOI: 10.1016/j.drugalcdep.2020.108179
|View full text |Cite
|
Sign up to set email alerts
|

The short-acting synthetic cannabinoid AB-FUBINACA induces physical dependence in mice

Abstract: Background: Recent years have seen a rise in the diversity and use of synthetic cannabinoids. The present study evaluated the behavioral effects of the third-generation indazole-3-carboxamide-type synthetic cannabinoid, AB-FUBINACA. Methods: Adult male and female C57BL/6J mice were treated with AB-FUBINACA (0–3 mg/kg, i.p.) and tested repeatedly in the tetrad battery measuring catalepsy, antinociception, hypothermia, and locomotor activity. Mice treated with AB-FUBINACA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Our results revealed that intraperitoneal injection of MDMB-PINACA mixed with clozapine induced tetrad effect in mice by showing hypolocomotion and cataleptic effect at high doses, besides hypothermia and antinoception with both high and low doses which supported by [11] who reported that use of synthetic cannabinoids AB-FUBINACA induced classic cannabinoid effects in tetrad tests. The reduced locomotor activity at high doses and increased locomotor activity at low doses which run in parallel with previous studies that reported a dose-dependent locomotor effects with AB-FUBINACA, AB-PINACA, PB-22 and THC cannabinoids [23] & [24] & [25].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results revealed that intraperitoneal injection of MDMB-PINACA mixed with clozapine induced tetrad effect in mice by showing hypolocomotion and cataleptic effect at high doses, besides hypothermia and antinoception with both high and low doses which supported by [11] who reported that use of synthetic cannabinoids AB-FUBINACA induced classic cannabinoid effects in tetrad tests. The reduced locomotor activity at high doses and increased locomotor activity at low doses which run in parallel with previous studies that reported a dose-dependent locomotor effects with AB-FUBINACA, AB-PINACA, PB-22 and THC cannabinoids [23] & [24] & [25].…”
Section: Discussionsupporting
confidence: 83%
“…(B) Body temperature Body temperature was measured by taking rectal temperature using digital thermometer to assess incidence of hypothermia. Basal rectal temperature was recorded 5minutes before drug administration and 50 minutes after [10] & [11].…”
Section: ) Tetrad Assessment (A) Locomotor Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to adverse reactions of these compounds observed in rodent studies (catalepsy, hypothermia, dose-dependent and inconsistent effect on locomotor activity, agitation, anxiety), as well as those reported in humans (agitation, anxiety, hallucinations), these substances have never been recorded in therapy. However, the previously mentioned compounds are found as "impurities" in various trafficked preparations, especially on the black market, or used as street drugs [65]. CB1R are located in presynaptic neurons in various regions of the CNS, such as the cerebral cortex, hippocampus, hypothalamus, cerebellum, globus pallidus, and mesencephalic periaqueductal gray matter.…”
Section: The Psychotropic Properties Of Benzydamine Linked To Cannabi...mentioning
confidence: 99%
“…The doses of AMB-FUBINACA treated groups were selected as Group III received the lowest dose 2.5mg/kg which was confirmed to occupy all cannabinoid receptors with no or little clinical effect according to (Wilson et al, 2019;Trexler et al, 2020), Group V received the highest dose 10 mg/kg which cause confirmed toxicity and tolerated by animals according to ( Mousa et al,2021;Wilson et al, 2019) and Group IV received dose 5mk/kg midway between the lowest and the highest dose according to (Hsin-Hung Chen et al, 2016) .…”
Section: Animalsmentioning
confidence: 99%